Plasma Exchange Downregulates Activated Monocytes and Restores Regulatory T Cells in Kawasaki Disease. Issue 1 (21st September 2018) - Koizumi, Keiichi; Hoshiai, Minako; Moriguchi, Takeshi; Katsumata, Nobuyuki; Toda, Takako; Kise, Hiroaki; Hasebe, Yohei; Kono, Yosuke; Sunaga, Yuto; Yoshizawa, Masashi; Watanabe, Atsushi; Harii, Norikazu; et al.
Abstract: In Kawasaki disease (KD), the effect of plasma exchange (PE) on immune cells has not been fully elucidated. Therefore, we examined the changes in the number of CD14 + CD16 + activated monocytes, regulatory T (Treg ), and T‐helper type 17 (Th17) cells in KD patients treated with PE. The percentage of total monocytes and subclasses of lymphocytes, including CD4 + and CD8 + T cells, and CD19 + B cells, showed no significant difference before and after PE. However, the percentage of CD14 + CD16 + monocytes in total leukocytes decreased significantly after PE (1.1% ± 1.5% vs. 2.1% ± 2.3%, P  < 0.05). Furthermore, while the percentage of Th17 cells in CD4 + T cells did not change, the percentage of Treg cells in CD4 + T cells increased significantly after PE (11.1% ± 5.1% vs. 8.0% ± 4.4%, P  < 0.05). Therefore, PE downregulates activated monocytes and upregulates Treg cells toward normal levels and thus attenuates inflammation in KD.